Qualitative Study to Understand Pediatric Hospitalists and Emergency Medicine Physicians' Perspectives of Clinical Pathways. Issue 2 (March 2020) - O'Hara, Kimberly; Tanverdi, Melisa; Reich, Jennifer; Scudamore, D. David; Tyler, Amy; Bakel, Leigh Anne
Abstract : Introduction: Healthcare costs are rising, and clinical pathways (CPW) are one means to promote high-value care by standardizing care and improving outcomes without compromising cost or quality. However, providers do not always follow CPW, and our understanding of their perceptions is limited. Our objective was to examine pediatric hospital medicine (PHM) and pediatric emergency medicine (PEM) physician perspectives of CPW. Methods: We conducted semistructured, in-depth, one-on-one qualitative interviews with PHM and PEM physicians between February 2017 and August 2017. Interviews were audio-recorded, professionally transcribed, and accuracy verified. Using an inductive analytic strategy, we systematically coded the data to identify themes. Results: We interviewed 15 PHM and 15 PEM physicians. These providers identified many benefits and limitations of CPW, which positively or negatively impact resource utilization, communication, education of personnel, patients, and families, as well as practice behaviors and attitudes. Perceived benefits included (1) reduction of unnecessary utilization, (2) standardization of care, (3) improved communication, (4) education of oneself and others, and (5) confidence and validation when actions align with CPW. Limitations of CPW were (1) resource utilization for revisions, updates, and dissemination; (2) "tunnel vision" and cognitive biases; (3) loss of autonomy; (4) prescriptive medicine; (5) information overload; (6) pressure to adhere; and (7) guilt if actions do not align with CPW. Conclusions: CPW are tools with advantages and disadvantages that are used and viewed differently by providers. Such insight into how physicians perceive CPW may help to optimize hospital improvement work and enhance high-value care.